2017
DOI: 10.1085/jgp.201711795
|View full text |Cite
|
Sign up to set email alerts
|

Integrative model of coronary flow in anatomically based vasculature under myogenic, shear, and metabolic regulation

Abstract: Coronary blood flows through a complex vasculature that is regulated by a number of physiological mechanisms, including myogenic, shear regulation, and metabolic control. Namani et al. describe a fully integrative and anatomically correct model that accurately predicts experimental observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 104 publications
(183 reference statements)
0
46
0
Order By: Relevance
“…The four model parameters are: (1) the maximum decrease in vessel radius (or the peak amplitude), ρ m ; (2) ϕ m is the transvascular pressure at which the vessel radius decreases by ρ m (the pressure at peak amplitude); (3) the pressure bandwidth of the vessel radius change is C m (Namani et al, 2018 ); (4) and the exponent, m , is assumed to be 2.0 (Young et al, 2012 ).…”
Section: Collecting and Analyzing Existing Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The four model parameters are: (1) the maximum decrease in vessel radius (or the peak amplitude), ρ m ; (2) ϕ m is the transvascular pressure at which the vessel radius decreases by ρ m (the pressure at peak amplitude); (3) the pressure bandwidth of the vessel radius change is C m (Namani et al, 2018 ); (4) and the exponent, m , is assumed to be 2.0 (Young et al, 2012 ).…”
Section: Collecting and Analyzing Existing Datamentioning
confidence: 99%
“…The model of Cornelissen and colleagues incorporated a network of vessels with diameter-dependent myogenic responses and generated theoretical pressure-flow curves with prominent autoregulation (Cornelissen et al, 2000 , 2002 ). Most recently, Namani et al provided an integrative model of coronary flow based on a realistic anatomy, active and passive flow determinants, and myogenic reactivity data (Namani et al, 2018 ). While important mechanistic insights were provided by these studies, a limitation of the previous modeling efforts is that they relied upon data from dissimilar species and/or ex vivo active autoregulation data (i.e., isolated hearts in which coronary flow typically exceeds values seen in vivo ).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of autoregulation may affect results presented in this study (Meier et al, 2004 ). It will also permit testing of further factors that affect local and global flow, as shown recently by Namani et al ( 2018 ).…”
Section: Limitationsmentioning
confidence: 88%
“…A shortcoming in that work was the limitation to topology, ignoring the 3D distribution over the myocardium. More extensive work came from the group of Kassab, who in a series of studies described these characteristics in the arterial, capillary, and venous coronary bed of pigs, also based on corrosion casts, followed by extensive modeling and hemodynamic analyses (Kassab et al, 1993(Kassab et al, , 1999Kassab and Fung, 1994;Kalsho and Kassab, 2004;Kassab, 2005;Mittal et al, 2005a,b;Kaimovitz et al, 2008;Namani et al, 2018). Following initial work on manual segmentation of the coronary vasculature based on corrosion casts, our lab has developed an imaging cryomicrotome that allows for extensive 3D recording of branching structures (Spaan et al, 2005) and applied this technique for the study of network characteristics in several species and organs (van Horssen et al, 2010(van Horssen et al, , 2014van den Wijngaard et al, 2011;Hakimzadeh et al, 2014;Bedussi et al, 2015;Schwarz et al, 2017), culminating in the current work on the human heart.…”
Section: Previous Datamentioning
confidence: 99%
“…In the beating heart, systolic flow in notably the subendocardium is impaired by the contracting surrounding myocardium (Hoffman and Spaan, 1990). In a model study, Namani et al showed that not only is flow higher under passive conditions than under autoregulation, but that ignoring the interaction between vessels and the surrounding myocardium indeed results in increased flow and thus perfusion estimates (Namani et al, 2018). Bache et al found an increase in the subendocardium/subepicardium perfusion ratio with decreasing heart rate at maximal vasodilation (Bache and Cobb, 1977).…”
Section: Hemodynamic Predictionsmentioning
confidence: 99%